Use of arteriography for the initial evaluation of patients with intermittent lower limb claudication - Wolosker, Nelson; Rosoky, Ruben Ayzin; Nishinari, Kenji; Nakano, Lívio (São Paulo Medical Journal, 2001)
CONTEXT: Many patients with intermittent claudication continue to be forwarded to the vascular surgeon for initial evaluation after arteriography has already been accomplished. OBJECTIVE: The main objective of this work was to analyze the usefulness and the need for this procedure. TYPE OF STUDY: Retrospective study. SETTING: The patients were divided into two groups: Group 1, with the arteriography already performed and Group 2 without the initial arteriography. PARTICIPANTS: One hundred patients with intermittent claudication were retrospectively studied. Other specialists had forwarded them for the first evaluation of intermittent claudication, without any previous treatment. MAIN MEASUREMENTS: All patients were treated clinically for at least a 6-month period. The total number of arteriographies performed in the two groups was compared and the need and usefulness of the initial arteriography (of Group 1) was also analyzed. RESULTS: The evolution was similar for both groups. The total number of arteriographies was significantly higher in Group 1 (Group 1 with 53 arteriographies vs. Group 2 with 7 arteriographies). For this group, it was found that arteriography was only useful in five cases (10%), because the surgeries were based on their findings. However, even in those cases, no need for arteriography was observed, as the procedure could have been performed at the time of surgical indication. CONCLUSION: There are no indications for arteriography in the early evaluation of patients with intermittent claudication, because it does not modify the initial therapy, independent of its result. In cases where surgical treatment is indicated, this procedure should only be performed prior to surgery.